REHABILITASI PSIKOLOGIS DAN REKONSTRUKSI PEMUKIMAN PENDUDUK KORBAN BENCANA GEMPA PASAMAN - Uning Pratimaratri; Yulcherina Yulcherina; Pebriyenni Pebriyenni (LPPM STAIMAS WONOGIRI, 2022)
The earthquake that occurred in Pasaman Regency on February 28, 2022 caused casualties and damage to houses, gardens, and other infrastructure. During the emergency response time, the earthquake victims lived in emergency tents because the existing houses were uninhabitable. Many people's houses were severely damaged due to the construction of houses that were not up to standard. The objectives of community service activities are to: (1) provide temporary shelter for victims of the Pasaman earthquake; (2) increasing public understanding of the correct structure of housing, and safe from the risk of earthquake disasters; (3) Recovering earthquake victims from trauma, so that they get up and start their daily activities. (4) Easing the burden on victims by providing logistical assistance. Activities are carried out using a participatory method. As planned, after the activity several things were achieved: (1) the availability of a shelter building for one family; (2) Public understanding of the correct building structure increases; (3) Children who are victims of natural disasters regain their spirits and rise from trauma; (4) Logistics assistance can ease the burden of earthquake victims ahead of the month of Ramadan. The implication of Community Service activities is to reduce the burden of the Regional Government in restoring the economic condition of the community after the earthquake. With the participation of the community together there is an acceleration of recovery. After the activities were carried out, it was concluded that post-earthquake handling requires the participation of various parties, for that it is necessary to coordinate with various parties to avoid overlapping.